Physicochemical Analysis of Yoghurt with Red Dragon Fruit Juice-Ants' Nest Extract and Sucrose-Fructose Proportion - Noorzantika, Istyani Fitria; Dwiyanti, Hidayah; Prihananto, Vincentius (Program Studi Teknologi Pangan, 2024)
The development of goat's milk-based yoghurt with the addition of sucrose-fructose proportions, ant nest extract and red dragon fruit juice as an alternative functional food high in antioxidants and fiber. The aim of the research was to determine the effect of the proportion of sucrose-fructose, the effect of the concentration of ant nest extract and red dragon fruit juice (ESBN), as well as the interaction of the two factors on the physicochemical properties of yoghurt, and determine the best product based on the physicochemical properties of yoghurt. The research used a two-factor Randomized Group Design (RAK) experimental method namely: 1) Proportion of sucrose-fructose (100:0; 50:50; 0:100) and 2) Concentration of ant nest extract and red dragon fruit juice (1:2) (10%, 15%, 20%). Data analysis uses ANOVA with 95% confidence level with DMRT follow-up test if the differences are significant, and effectiveness index test to determine the best product. The analysis results show that the higher the proportion of sucrose, the viscosity of the yoghurt increases and the pH decreases. The higher the ESBN concentration, the higher the a* (redness), b* (yellowness), pH, crude fiber and antioxidant activity, as well as reducing the L* (lightness) and viscosity. The interaction of these two factors affects the viscosity and pH of yoghurt. The best treated yoghurt is P2K2 yoghurt (50% sucrose : 50% Fructose + 15% ESBN) which has a viscosity of 297.67 cP and a pH of 3.83.